The level of procalcitonin is a biomarker for differentiation between pathogenic and non-pathogenic bacteria - Deebukkham, Suwipar (Health Science Clinical Research, 2024)
Background: Sepsis is a condition in which microorganisms such as viruses, fungi, and pathogenic bacteria invade the bloodstream. When the body reacts to the foreign elements of the bacteria, accurate and timely diagnosis will lead to rapid treatment and appropriate antibiotic administration. Therefore, procalcitonin is a biomarker for helping to classify bacterial infections and monitor treatment. Methods: This is a retrospective description study in a group of samples who underwent medical laboratory tests to measure procalcitonin levels along with blood cultures and were admitted to Uttaradit Hospital between October 1, 2022 and October 31, 2023, totaling 934 cases. Results: The study found that the procalcitonin level of 0.1-0.5 ng/ml, 26 cases (13.2%), culture results were positive, 491 cases (66.7%), and procalcitonin level of 0.6-2.0 ng/ml had OR = 10.56 (95%CI:6.56-16.99), procalcitonin level >2.0 ng/ml had OR = 17.67 (95%CI: 10.81-28.86), and sexual status had OR1.01 (95%:CI:0.74-1.39), age group between 21-40 years had OR1.20 (95%CI:0.34-4.21), age group between 41-60 years had OR1.53 (95%CI:0.50-4.68). and the group aged over 60 years had an OR value of 1.80 (95%CI: 0.62-5.27). Conclusions: Using procalcitonin in conjunction with culture tests can improve diagnostic accuracy and help reduce unnecessary antibiotic use, allowing physicians to diagnose and treat patients promptly